Analisis Kinerja Pemandu Wisata Lokal dalam Kegiatan Praktikum Lapang Berbasis Project Based Learning di Provinsi Bali - Nadiah Rofifahtus Nurjannah; Matho Hatus Sahada; Vania Chusnul Azahra Biyantari; Hesty Rivkiyanti; Mohamad Alfaredo Kurniawan; Rafael Eka Putra Pasha; Juniar Prasetya Dwi Payana; Muhamad Ari Perdana (Jurnal Kajian Pariwisata Dan Perhotelan, 2026)
This study aims to evaluate the performance of local tour guides in Bali Province based on the preferences of tourists participating in a field practicum activity through a Project-Based Learning. The research employed a descriptive quantitative approach, with primary data collected through questionnaires distributed to 134 respondents divided into three bus groups. The evaluation of tour guide performance focused on five key dimensions: Professional Competence, Interpersonal Skills, Organization, Empathy, and Problem Solving. The findings indicate that the overall performance of local tour guides in Bali Province was categorized as “Very High”, with scores of 4.904 for Bus 1, 5.107 for Bus 2, and 5.154 for Bus 3. Specifically, the dimensions of Professional Competence, Interpersonal Skills, and Organization consistently achieved the “Very High” category across all groups. However, the Problem-Solving dimension received comparatively lower evaluations and was classified only as “High”. Several aspects were identified as areas for improvement, including tour guides’ responsiveness in handling technical issues such as scheduling and transportation-related problems, the efficiency of travel time management, and the provision of more detailed information regarding available facilities. Addressing these shortcomings is essential to minimize operational obstacles and enhance the overall effectiveness of tour implementation in the field.